2002
DOI: 10.1093/hmg/11.5.589
|View full text |Cite
|
Sign up to set email alerts
|

Coding haplotype analysis supports HCR as the putative susceptibility gene for psoriasis at the MHC PSORS1 locus

Abstract: PSORS1, near HLA-C, is the major genetic determinant of psoriasis. We present genetic and structural evidence suggesting a major role for the HCR gene at the PSORS1 locus. Genotyping of 419 families from six populations revealed that coding single-nucleotide polymorphisms of HCR formed a conserved allele HCR*WWCC that associated highly significantly with psoriasis and with the HLA-Cw6 allele in all populations. Because of strong linkage disequilibrium between HLA-Cw6 and HCR*WWCC, the two genes could not be ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 26 publications
7
137
1
Order By: Relevance
“…The human HCR gene maps to chromosome 6p21, in a region that is crucial for psoriasis vulgaris, located 111 kb towards the telomere of the HLA-C gene (Suomela et al, 2003). HCR is expressed differently in lesional psoriatic skin compared with normal skin (Asumalahti et al, 2002). HCR has also been identified as protein partner for StAR and hence has been named SBP (Sugawara et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human HCR gene maps to chromosome 6p21, in a region that is crucial for psoriasis vulgaris, located 111 kb towards the telomere of the HLA-C gene (Suomela et al, 2003). HCR is expressed differently in lesional psoriatic skin compared with normal skin (Asumalahti et al, 2002). HCR has also been identified as protein partner for StAR and hence has been named SBP (Sugawara et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The HCR gene was identified within the 111 kb telomeric region of the HLA-C gene, a crucial region for psoriasis vulgaris (Oka et al, 1999;Suomela et al, 2003). The direct involvement of HCR in psoriasis is currently being discussed (Asumalahti et al, 2000;O'Brien et al, 2001;Asumalahti et al, 2002;Elomaa et al, 2004). Using HCR-transgenic mice, a recent report suggested that HCR is a potential candidate gene for psoriasis susceptibility (Elomaa et al, 2004).…”
mentioning
confidence: 99%
“…Two genes lying within this interval have been intensively studied with respect to their role in psoriasis susceptibility. One is HCR (helix coiled coil rod homolog); 42 the other is corneodesmosin (CDSN/S). CDSN is expressed in terminally differentiated keratinocytes and in the inner root sheath of hair follicles.…”
Section: Psors1mentioning
confidence: 99%
“…4,5 The susceptibility region in chromosome 6 (PSORS1-psoriasis susceptibility 1) has refined to an approximately B300 kb region around HLA-C gene and contains several candidate genes including HLA-C, octamer transcription factor-3 (OTF3), transcription factor-19 (TCF19), corneodesmosin (CDSN) and a-helix coiled-coil rod homolog (HCR) genes. [6][7][8][9] In addition, several non-MHC psoriasis susceptibility loci (1q21, 16q and 17q) associate with different AIDs such as systemic lupus erythematosus, rheumatoid arthritis, Crohn's disease and diabetes. 10 This provides support for the hypothesis that susceptibility to different AIDs may be driven by the same susceptibility genes and immunopathways.…”
Section: Introductionmentioning
confidence: 99%